2019
DOI: 10.1186/s12936-019-2774-2
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 2D6 profiles and their relationship with outcomes of primaquine anti-relapse therapy in Australian Defence Force personnel deployed to Papua New Guinea and East Timor

Abstract: Background Primaquine, an 8-aminoquinoline with anti-hypnozoite activity against Plasmodium vivax , is metabolized by human cytochrome P450 2D6 (CYP2D6) to its active metabolite. Human CYP2D6 activities may influence the metabolism of primaquine and the risk of experiencing Plasmodium relapses following primaquine anti-relapse therapies (PART). In this study, the CYP2D6 profile and its relationship with outcomes of PART in Australian Defence Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Another study conducted by Spring et al 30 confirmed that subjects with CYP2D6 IM or PM phenotypes have reduced PQ metabolism compared to those with an NM phenotype. In contrast, Chen et al 31 found that CYP2D6 phenotype or activity scores were not significantly different between their relapse and non-relapse groups. One explanation of why the present study did not find a relationship between CYP2D6 genotype or metabolizer status and PQ response may be due to the coadministration of CQ.…”
Section: Discussionmentioning
confidence: 83%
“…Another study conducted by Spring et al 30 confirmed that subjects with CYP2D6 IM or PM phenotypes have reduced PQ metabolism compared to those with an NM phenotype. In contrast, Chen et al 31 found that CYP2D6 phenotype or activity scores were not significantly different between their relapse and non-relapse groups. One explanation of why the present study did not find a relationship between CYP2D6 genotype or metabolizer status and PQ response may be due to the coadministration of CQ.…”
Section: Discussionmentioning
confidence: 83%
“…The association of CYP2D6 and relapse has proved harder to confirm in areas of endemicity [19–24]. Two clinical trials found an increased risk of relapse with an AS-A of ≤1.0 [20, 21], yet in Australian soldiers contracting P. vivax while deployed, relapse was not associated with activity score [22]. This latter study, as well as 2 studies in Thailand [23, 24], found the NM phenotype in the majority of patients with relapse.…”
mentioning
confidence: 99%
“…We investigated the phenotypic activity of CYP2D6 and CYP2C19 in the course of acute vivax malaria, after completion of antiparasite chemotherapy with primaquine/chloroquine and during convalescence. CYP selection was guided by the evidence that CYP2D6 is the major pathway for conversion of primaquine into its active metabolite(s) [21][22][23][24][25][26][27] and by our previous findings of reduced CYP2C19 activity during the acute phase of visceral leishmaniosis. 16…”
mentioning
confidence: 99%